2009
DOI: 10.1542/peds.2008-2233l
|View full text |Cite
|
Sign up to set email alerts
|

Paying for Quality Care: Implications for Racial and Ethnic Health Disparities in Pediatric Asthma

Abstract: Children who are from racial and ethnic minority groups, are of low income, or are both are affected disproportionately by asthma. Despite advances in the treatment and management of asthma, including the development of guidelines for clinical practice, substantial racial, ethnic, and socioeconomic disparities exist in both health care quality and health outcomes. Financial incentives generally have the potential to improve overall quality and, when targeted specifically toward disparity reduction, may be able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Finally, the consistently documented association between health insurance and receipt of quality primary care in a medical home suggests the need for actions and reforms to maximize coverage but also to provide financial incentives to pediatric primary care practices through improved reimbursement mechanisms (AAP & Medical Home Initiatives for Children With Special Needs Project Advisory Committee, 2004, AAP Committee on Adolescence and Committee on Child Health Financing, 2009;James & Rosenbaum, 2009).…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…Finally, the consistently documented association between health insurance and receipt of quality primary care in a medical home suggests the need for actions and reforms to maximize coverage but also to provide financial incentives to pediatric primary care practices through improved reimbursement mechanisms (AAP & Medical Home Initiatives for Children With Special Needs Project Advisory Committee, 2004, AAP Committee on Adolescence and Committee on Child Health Financing, 2009;James & Rosenbaum, 2009).…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…Different patterns for prescribing steroids between Xiamen and Keelung may indicate potential differences in culture and people’s attitudes toward specific medications in Taiwan and China. Previous studies revealed national and racial disparities in the patient’s knowledge about asthma and its management [ 11 , 12 , 37 39 ]. South Asia parents tended to believe that inhaled corticosteroids did more harm than good when compared to the beliefs of Caucasian parents (OR 3.19, CI 1.22-8.34) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Path models are a useful method for assessing explanatory mechanisms with observed variables, and path is adjusted for all factors included in the model. 14 All equations were estimated simultaneously with Mplus 6.12 software. P-values of 0.05 or less were considered statistical significant for these analyses.…”
Section: Methodsmentioning
confidence: 99%